FAMM Flap in Reconstructing Postsurgical Nasopharyngeal Airway Stenosis - Nangole, Ferdinand Wanjala (Hindawi Publishing Corporation, 2014)
Introduction. Postsurgical nasopharyngeal airway stenosis can be a challenge to manage. The stenosis could be as a result of any surgical procedure in the nasopharyngeal region that heals extensive scarring and fibrosis. Objective. To evaluate patients with nasopharyngeal stenosis managed with FAMM flap. Study Design. Prospective study of patients with nasopharyngeal stenosis at the Kenyatta National Hospital between 2010 and 2013 managed with FAMM flap. Materials and Methods. Patients with severe nasopharyngeal airway stenosis were reviewed and managed with FAMM flaps at the Kenyatta National Hospital. Postoperatively they were assessed for symptomatic improvement in respiratory distress, patency of the nasopharyngeal airway, and donor site morbidity. Results. A total of 8 patients were managed by the authors in a duration of 4 years with nasopharyngeal stenosis. Five patients were managed with unilateral FAMM flaps in a two-staged surgical procedure. Four patients had complete relieve of the airway obstruction with a patent airway created. One patient had a patent airway created though with only mild improvement in airway obstruction. Conclusion. FAMM flap provides an alternative in the management of postsurgical severe nasopharyngeal stenosis. It is a reliable flap that is easy to raise and could provide adequate epithelium for the stenosed pharynx.